Zygotorulaspora florentina and Starmerella bacillaris in multistarter fermentation with Saccharomyces cerevisiae to reduce volatile acidity of high sugar musts. (19th December 2017) - Lencioni, L.; Taccari, M.; Ciani, M.; Domizio, P.
Abstract: Background and Aims: The possibility to decrease wine volatile acidity (VA) is an important aspect in wine production. This applies in particular to wines that are produced from musts with high sugar concentration, where the osmotic pressure promotes an increase in acetic acid production by Saccharomyces cerevisiae . This study aimed to identify suitable yeast strains and fermentation temperature to undertake the alcoholic fermentation of high sugar musts. Methods and Results: To lower VA during fermentation of high sugar musts, two non‐ Saccharomyces yeast strains, Zygotorulaspora florentina and Starmerella bacillaris, were used in multistarter fermentations with S. cerevisiae at a fermentation temperature of 14 and 20°C. The fermentation temperature influenced the yeast behaviour and the composition of the two mixed fermentations. Conclusions: Independent of fermentation temperature, the mixed fermentations with Z. florentina performed best to reduce VA. Significance of the Study: Mixed fermentations with the non‐ Saccharomyces yeast strains Z. florentina and S. bacillaris may represent a valuable approach for the fermentation of high sugar musts.